ASKAP detection of periodic and elliptically polarized radio pulses from UV Ceti. Issue 1 (28th June 2019) - Zic, Andrew; Stewart, Adam; Lenc, Emil; Murphy, Tara; Lynch, Christene; Kaplan, David L; Hotan, Aidan; Anderson, Craig; Bunton, John D; Chippendale, Aaron; Mader, Stacy; Phillips, Chris
ABSTRACT: Active M dwarfs are known to produce bursty radio emission, and multiwavelength studies have shown that solar-like magnetic activity occurs in these stars. However, coherent bursts from active M dwarfs have often been difficult to interpret in the solar activity paradigm. We present Australian Square Array Pathfinder (ASKAP) observations of UV Ceti at a central frequency of 888 MHz. We detect several periodic, coherent pulses occurring over a time-scale consistent with the rotational period of UV Ceti. The properties of the pulsed emission show that they originate from the electron cyclotron maser instability, in a cavity at least 7 orders of magnitude less dense than the mean coronal density at the estimated source altitude. These results confirm that auroral activity can occur in active M dwarfs, suggesting that these stars mark the beginning of the transition from solar-like to auroral magnetospheric behaviour. These results demonstrate the capabilities of ASKAP for detecting polarized, coherent bursts from active stars and other systems.